Perancangan Kawasan Pantai Puri Gading Yang Tanggap Terhadap Potensi Bencana Tsunami Di Kota Bandar Lampung - Afinda Sugara, Chelvin; Wilfritz Soaduon Panjaitan, Tigor; Rolalisasi, Andarita (Jurnal Etnik: Ekonomi-Teknik, 2023)
One of the natural disasters that can occur in Indonesia is a tsunami caused by geological factors. Indonesia is an area located on the "Ring of Fairness" or the circle of fire, which is an area that often experiences earthquakes and volcanic eruptions. Natural disasters that can occur in Indonesia are caused by geological and hydrometeorological factors. Volcanoes and earthquakes are caused by the collision of the Eurasian, Australian and Pacific plates on the active plate which is also the meeting place for the three plates. In this case disaster management is a dynamic, integrated and sustainable process. The aim is to improve the quality of measures related to various activities, such as disaster prevention, impact mitigation, preparedness, emergency response, victim evacuation, and rebuilding damaged areas. One way to be prepared for natural disasters is to design areas so that they are more likely to be protected from them. In the case of Puri Gading Beach in Lampung, the authors have used a disaster-prone area (KRB) mitigation approach to ensure that the area is protected from the Tsunami. There are two types of tsunami management strategies based on disaster reduction in the City of Bandar Lampung which are prone to natural disasters, namely: (1). Structural mitigation in the form of explaining the construction of flood protection buildings such as the construction of embankments, the construction of drainage network structures, and the construction of drop structures; (2) Mitigation of non-structural disasters in the form of disaster mitigation training and simulations, as well as assessment of the impact of natural disaster reduction on risk reduction policies for affected areas in Bandar Lampung City, Lampung, Indonesia.